Desarrollo de un módulo visualizador de archivos con audioconferencia para integrarlo a la plataforma moodle y configuración de un entorno virtual de aprendizaje vía web. - García Sánchez, Diego Hernán (2011)
As a result of this research was implemented a virtual learning environment adapted to the requirements of the National College "November 26" Zaruma city, and also has an integrated audio conferencing module with a file viewer to improve communication between teachers and students, thus contributing to the teaching / learning process. We used the software development methodology XP, to use an agile, fast, flexible and quality, simple design and can work directly with the user. The phases of the methodology are as follows: Exploration: the client was raised with stories of the user and developers familiar with the tools we used. Planned Delivery: set the priority of each user stories, we estimated the effort and found the supply of the progress of the module. Iterations: were determined programming tasks to perform each iteration and make deliveries. Production: We performed tests and maintenance checks to determine the quality of software. Maintenance: While the tests were kept the system running and took out the correction of errors found in the production phase. Project Death: When you have met the needs of the client and the system was ready for operation. Audiovisor module development included the large number of modules that exist for the platform Moodle, that adapts itself directly to the needs of the institution in which the project has been carried out. Previously carried out the installation and configuration of Moodle for the institution meeting the needs of users who will use the system. Benefited from the boom in the use of flash in most web browsers and servers to develop our audiovisor module, and also used the ease of learning and use the PHP language. Audiovisor module allows streaming audio and video from the user teacher to student users connected to it, also has an online file viewer to view documents without opening an external application or file download required. This module integrates the Moodle Virtual Learning Environment of the institution to use it within the classes they need to use it.